60 years of glacier elevation and mass changes in the Maipo River Basin, central Andes of Chile - Farías Barahona, David; Ayala, Álvaro; Bravo, Claudio; Vivero, Sebastián; Seehaus, Thorsten; Vijay, Saurabh; Schaefer, Marius; Buglio, Franco; Casassa, Gino; Braun, Matthias (Remote Sensing, 2020)
Glaciers in the central Andes of Chile are fundamental freshwater sources for ecosystems and communities. Overall, glaciers in this region have shown continuous recession and down-wasting, but long-term glacier mass balance studies providing precise estimates of these changes are scarce. Here, we present the first long-term (1955-2013/2015), region-specific glacier elevation and mass change estimates for the Maipo River Basin, from which the densely populated metropolitan region of Chile obtains most of its freshwater supply. We calculated glacier elevation and mass changes using historical topographic maps, Shuttle Radar Topography Mission (SRTM), TerraSAR-X add-on for Digital Elevation Measurements (TanDEM-X), and airborne Light Detection and Ranging (LiDAR) digital elevation models. The results indicated a mean regional glacier mass balance of-0.12 ± 0.06 m w.e. a-1, with a total mass loss of 2.43 ± 0.26 Gt for the Maipo River Basin between 1955-2013. The most negative glacier mass balance was the Olivares sub-basin, with a mean value of-0.29 ± 0.07mw.e. a-1. We observed spatially heterogeneous glacier elevation and mass changes between 1955 and 2000, and more negative values between 2000 and 2013, with an acceleration in ice thinning rates starting in 2010, which coincides with the severe drought. Our results provide key information to improve glaciological and hydrological projections in a region where water resources are under pressure.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Central Andes; Glacier elevation changes; Glacier mass balance; InSAR; LiDAR; Mountain glaciers

Climate and surface mass balance of Mocho Glacier, Chilean Lake District, 40°S - Schaefer, Marius; Luis Rodriguez, Jose; Scheiter, Matthias; Casassa, Gino (Journal of Glaciology, 2017)
We present climate data, direct surface mass balance (SMB) observations and model results for Mocho Glacier in the Chilean Lake District. Mean annual temperature on a nunatak of Mocho Glacier at an elevation of ∼2000 m was +2.6°C in 2006-15 and mean annual precipitation in Puerto Fuy (13 km from the glacier, at an elevation of 600 m) was 4000 mm for the same period. High interannual variations in the SMB of Mocho Glacier were observed. A simple SMB model is able to reproduce the observed annual variations in SMB, but fails to predict the steep observed mass-balance gradient. The average of the measured annual glacier mass balances in the four hydrological years 2009/10-2012/13 was -0.90 m w.e. a-1 and the average modelled annual glacier mass balance 2006/07-2014/15 was -1.05 m w.e. a-1. The observed distributed ablation shows a clear altitudinal dependency, while accumulation is determined by patterns of snow drift as well. These patterns are only poorly represented in the model and have to be included in order to be able to reproduce a realistic SMB map of the glacier.
Created from Fastlane, Scopus look-up
Keywords: glaciological method; mountain glaciers; numerical modelling; surface mass balance

Climate’s firm grip on glacier ablation in the Cordillera Darwin Icefield, Tierra del Fuego - Temme, Franziska; Sommer, Christian; Schaefer, Marius; Jaña, Ricardo; Arigony-Neto, Jorge; Gonzalez, Inti; Izagirre, Eñaut; Giesecke, Ricardo; Tetzner, Dieter; Fürst, Johannes (Nature Communications, 2025)
The Cordillera Darwin Icefield (CDI) in Tierra del Fuego is one of the largest temperate ice bodies in the Southern Hemisphere. We simulate the climatic energy and mass balance of its glaciers (2000–2023), which are sensitive indicators of climatic changes in the Southern Hemisphere’s higher mid-latitudes. Year-round westerly winds cause strong climatic gradients across the mountain range, reflected in the energy and mass fluxes. Our results reveal a significant increase in surface melt (+0.18 m w.e. yr-1 per decade) over the past two decades. We also present the first estimate of dynamically controlled mass loss into adjacent fjords and lakes by frontal ablation, amounting to 1.44 ± 0.94 Gt yr-1 (26 % of the total CDI mass loss). Frontal losses are mainly channelized through few marine-terminating glaciers. While frontal ablation is important for predicting the fate of individual glaciers, for the CDI as a whole, atmospheric conditions exert the main control on the current glacier evolution.
CRIS-Team Scopus Importer:2025-04-01

Editorial: Climate Impacts on Glaciers and Biosphere in Fuego-Patagonia - Schneider, Christoph; Braun, Matthias; Schaefer, Marius; Grießinger, Jussi; Casassa, Gino (Frontiers in Earth Science, 2020)
CRIS-Team Scopus Importer:2020-05-05
Keywords: biosphere; climate change; climate variability; cryosphere; Patagonia; Tierra del Fuego

Frontal ablation and mass loss of the Patagonian icefields - Minowa, Masahiro; Schaefer, Marius; Sugiyama, Shin; Sakakibara, Daiki; Skvarca, Pedro (Earth and Planetary Science Letters, 2021)
The complex dynamics of calving glaciers is a major uncertainty in projecting global glacial mass loss. We present frontal ablation and ice mass change for the 38 major calving glaciers in the Patagonian icefields based on remote-sensing observations of ice-front positions, surface speeds and elevation changes. The frontal ablation from 2000 to 2019 was -24.1 +/- 1.7 Gt a(-1), which represents 34 +/- 6% of the total ablation of the icefields. The fraction of frontal ablation was close to half in the southern icefield and about one fifth in the northern icefield. The rate of the mass loss from the icefields during the period of study was 15.2 +/- 3.5 Gt a(-1), which is generally explained by surface mass balance but was accelerated as a result of increasing frontal ablation. The frontal ablation and mass change values suggest surface mass balance to be -1.5 +/- 0.9 Gt a(-1) for the northern icefield and +11.5 +/- 2.7 Gt a(-1) for the southern icefield during this period. Our study demonstrates that a strong increase in frontal ablation at several glaciers drives the mass loss in the southern icefield, whereas increasingly negative surface mass balance drives the mass loss in the northern icefield. (C) 2021 Elsevier B.V. All rights reserved.
Created from Fastlane, WoS look-up

Geodetic Mass Balances and Area Changes of Echaurren Norte Glacier (Central Andes, Chile) between 1955 and 2015 - Farías Barahona, David; Vivero, Sebastián; Casassa, Gino; Schaefer, Marius; Burger, Flavia; Seehaus, Thorsten; Iribarren-Anacona, Pablo; Escobar, Fernando; Braun, Matthias (Remote Sensing, 2019)
The Echaurren Norte Glacier is a reference glacier for the World Glacier Monitoring Service (WGMS) network and has the longest time series of glacier mass balance data in the Southern Hemisphere. The data has been obtained by the direct glaciological method since 1975. In this study, we calculated glacier area changes using satellite images and historical aerial photographs, as well as geodetic mass balances for different periods between 1955 and 2015 for the Echaurren Norte Glacier in the Central Andes of Chile. Over this period, this glacier lost 65% of its original area and disaggregated into two ice bodies in the late 1990s. The geodetic mass balances were calculated by differencing digital elevation models derived from several sources. The results indicated a mean cumulative glacier wide mass loss of −40.64 ± 5.19 m w.e. (−0.68 ± 0.09 m w.e. a−1). Within this overall downwasting trend, a positive mass balance of 0.54 ± 0.40 m w.e. a−1 was detected for the period 2000–2009. These estimates agree with the results obtained with the glaciological method during the same time span. Highly negative mass change rates were found from 2010 onwards, with −1.20 ± 0.09 m w.e. a−1 during an unprecedented drought in Central Andes of Chile. The observed area and the elevation changes indicate that the Echaurren Norte Glacier may disappear in the coming years if negative mass balance rates prevai
Keywords: glacier mass balance; geodetic method; LiDAR; central Andes; glacier mapping; mountain glacier

Glacial lakes of the Central and Patagonian Andes - Wilson, Ryan; Glasser, Neil F.; Reynolds, John M.; Harrison, Stephan; Anacona, Pablo Iribarren; Schaefer, Marius; Shannon, Sarah (Global and Planetary Change, 2018)
The prevalence and increased frequency of high-magnitude Glacial Lake Outburst Floods (GLOFs) in the Chilean and Argentinean Andes suggests this region will be prone to similar events in the future as glaciers continue to retreat and thin under a warming climate. Despite this situation, monitoring of glacial lake development in this region has been limited, with past investigations only covering relatively small regions of Patagonia. This study presents new glacial lake inventories for 1986, 2000 and 2016, covering the Central Andes, Northern Patagonia and Southern Patagonia. Our aim was to characterise the physical attributes, spatial distribution and temporal development of glacial lakes in these three sub-regions using Landsat satellite imagery and image datasets available in Google Earth and Bing Maps. Glacial lake water volume was also estimated using an empirical area-volume scaling approach. Results reveal that glacial lakes across the study area have increased in number (43%) and areal extent (7%) between 1986 and 2016. Such changes equate to a glacial lake water volume increase of 65 km3 during the 30-year observation period. However, glacial lake growth and emergence was shown to vary sub-regionally according to localised topography, meteorology, climate change, rate of glacier change and the availability of low gradient ice areas. These and other factors are likely to influence the occurrence of GLOFs in the future. This analysis represents the first large-scale census of glacial lakes in Chile and Argentina and will allow for a better understanding of lake development in this region, as well as, providing a basis for future GLOF risk assessments.
Created from Fastlane, Scopus look-up
Keywords: Central Chile; Glacial lake inventory; GLOFs; Patagonia; Remote sensing

Glacier protection laws: Potential conflicts in managing glacial hazards and adapting to climate change - Iribarren-Anacona, Pablo; Kinney, Josie; Schaefer, Marius; Harrison, Stephan; Wilson, Ryan; Segovia, Alexis; Mazzorana, Bruno; Guerra, Felipe; Farías Barahona, David; Reynolds, John; Glasser, Neil (Ambio, 2018)
The environmental, socioeconomic and cultural significance of glaciers has motivated several countries to regulate activities on glaciers and glacierized surroundings. However, laws written to specifically protect mountain glaciers have only recently been considered within national political agendas. Glacier Protection Laws (GPLs) originate in countries where mining has damaged glaciers and have been adopted with the aim of protecting the cryosphere from harmful activities. Here, we analyze GPLs in Argentina (approved) and Chile (under discussion) to identify potential environmental conflicts arising from law restrictions and omissions. We conclude that GPLs overlook the dynamics of glaciers and could prevent or delay actions needed to mitigate glacial hazards (e.g. artificial drainage of glacial lakes) thus placing populations at risk. Furthermore, GPL restrictions could hinder strategies (e.g. use of glacial lakes as reservoirs) to mitigate adverse impacts of climate change. Arguably, more flexible GPLs are needed to protect us from the changing cryosphere.<br

Modeling past and future surface mass balance of the Northern Patagonia Icefield - Schaefer, Marius; Machguth, Horst; Falvey, M.; Casassa, Gino (Journal of Geophysical Research F: Earth Surface, 2013)
Glaciers are strongly retreating and thinning in Patagonia. We present new inferences about the climatic situation and the surface mass balance on the Northern Patagonia Icefield in the past and the future using a combined modeling approach. The simulations are driven by NCAR/NCEP Reanalysis and ECHAM5 data, which were physically downscaled using the Weather Research and Forecasting regional climate model and simple sub-grid parameterizations. The surface mass balance model was calibrated with geodetic mass balance data of three large non-calving glaciers and with point mass balance measurements. An increase of accumulation on the Northern Patagonia Icefield was detected from 1990-2011 as compared to 1975-1990. Using geodetic mass balance data, calving losses from the Northern Patagonia Icefield could be inferred, which doubled in 2000-2009 as compared to 1975-2000. The 21st century projection of future mass balance of the Northern Patagonia Icefield shows a strong increase in ablation from 2050 and a reduction of solid precipitation from 2080, both due to higher temperatures. The total mass loss in the 21st century is estimated to be 592±50 Gt with strongly increasing rates towards the end of the century. The prediction of the future mass balance of the Northern Patagonia Icefield includes several additional sources of errors due to uncertainties in the prediction of future climate and due to possible variations in ice dynamics, which might modify the geometry of the icefield and change the rate of mass losses due to calving. ©2013. American Geophysical Union. All Rights Reserved.
Created from Fastlane, Scopus look-up
Keywords: glacier; mass balance; Patagonia; sea-level rise

Morphological characterization of a highly-dynamic fluvial landscape: The River Baker (Chilean Patagonia) - Ulloa, H.; Mazzorana, B.; Batalla, R. J.; Jullian, C.; Iribarren-Anacona, P.; Barrientos, G.; Reid, B.; Oyarzun, C.; Schaefer, Marius; Iroume, Andres (Journal of South American Earth Sciences, 2018)
Characterizing river corridors from a hydro-morphological standpoint is a fundamental requisite for the analysis of their past evolution and for the plausible prediction of how rivers may adjust to changing climatic conditions and to increasing human impacts. The River Baker (Chilean Patagonia) is a highly dynamic fluvial system with relatively limited human intervention, which flows throughout a mountainous landscape following a narrow floodplain which widens towards the Pacific Ocean. Here, we characterize its current morphology as a basis for understanding its geomorphic dynamics, using satellite images as data source and following a hierarchical classification procedure. The Baker was divided into 9 segments and 34 reaches based on channel confinement and geometry. The geomorphic classification resulted in several confined (41%) and semiconfined (53%) reaches, whereas only 6% of them were classified as unconfined. Most of the confined reaches were single thread and the majority of the semiconfined ones were sinuous. Braided reaches were identified in all confinement categories and represent 30% of the reaches. We identified and characterized 246 islands and 393 fluvial bars and delimited 170 wetlands. Finally, we could statistically relate the island density to the braiding index, active channel width and sinuosity index, whereas the presence of bars is influenced by the active channel width, and degree of braiding and sinuosity. This characterization represents a starting point in the geomorphological analysis of the river and serves as a basis to plan future investigation efforts aiming at unravelling the morpho-dynamics of this unexplored large austral fluvial system.
Created from Fastlane, Scopus look-up
Keywords: Chilean patagonia; IDRAIM; River Baker; River morphology

Quantifying mass balance processes on the Southern Patagonia Icefield - Schaefer, Marius; Machguth, Horst; Falvey, M.; Casassa, Gino; Rignot, Eric (Cryosphere, 2015)
We present surface mass balance simulations of the Southern Patagonia Icefield (SPI) driven by downscaled reanalysis data. The simulations were evaluated and interpreted using geodetic mass balances, measured point balances and a complete velocity field of the icefield for spring 2004. The high measured accumulation of snow of up to 15.4 m w.e. yrg'1 (meters water equivalent per year) as well as the high measured ablation of up to 11 m w.e. yrg'1 is reproduced by the model. The overall modeled surface mass balance was positive and increasing during 1975-2011. Subtracting the surface mass balance from geodetic balances, calving fluxes were inferred. Mass losses of the SPI due to calving were strongly increasing from 1975-2000 to 2000-2011 and higher than losses due to surface melt. Calving fluxes were inferred for the individual glacier catchments and compared to fluxes estimated from velocity data. Measurements of ice thickness and flow velocities at the glaciers' front and spatially distributed accumulation measurements can help to reduce the uncertainties of the different terms in the mass balance of the Southern Patagonia Icefield.
Created from Fastlane, Scopus look-up

Simulations of the dynamics of the Northern Patagonian Ice Field, Chile チリ・北パタゴニア氷原のダイナミクスに関する数値シミュレーション - Schaefer, Marius; Greve, Ralf; Fürst, Johannes; Tabone, Ilaria; Braun, Matthias (JSSI & JSE Joint Conference, 2022)
CRIS-Team Scopus Importer:2024-12-16

Subglacial discharge controls seasonal variations in the thermal structure of a glacial lake in Patagonia - Sugiyama, Shin; Minowa, Masahiro; Fukamachi, Yasushi; Hata, Shuntaro; Yamamoto, Yoshihiro; Sauter, Tobias; Schneider, Christoph; Schaefer, Marius (Nature Communications, 2021)
Water temperature in glacial lakes affects underwater melting and calving of glaciers terminating in lakes. Despite its importance, seasonal lake temperature variations are poorly understood because taking long-term measurements near the front of calving glaciers is challenging. To investigate the thermal structure and its seasonal variations, we performed year-around temperature and current measurement at depths of 58–392 m in Lago Grey, a 410-m-deep glacial lake in Patagonia. The measurement revealed critical impacts of subglacial discharge on the lake thermal condition. Water below a depth of 100 m showed the coldest temperature in mid-summer, under the influence of glacial discharge, whereas temperature in the upper layer followed a seasonal variation of air temperature. The boundary of the lower and upper layers was controlled by the depth of a sill which blocks outflow of dense and cold glacial meltwater. Our data implies that subglacial discharge and bathymetry dictate mass loss and the retreat of lake-terminating glaciers. The cold lakewater hinders underwater melting and facilitates formation of a floating terminus.
CRIS-Team Scopus Importer:2021-11-12

Surface energy fluxes on Chilean glaciers: measurements and models - Schaefer, Marius; Fonseca-Gallardo, Duilio; Farías Barahona, David; Casassa, Gino (Cryosphere, 2020)
The surface energy fluxes of glaciers determine surface melt, and their adequate parametrization is one of the keys to a successful prediction of future glacier mass balance and freshwater discharge. Chile hosts glaciers in a large range of latitudes under contrasting climatic settings: from 18 degrees S in the Atacama Desert to 55 degrees S on Tierra del Fuego. Using three different methods, we computed surface energy fluxes for five glaciers which represent the main glaciological zones of Chile. We found the main energy sources for surface melt change from the Central Andes, where the net shortwave radiation is driving the melt, to Patagonia, where the turbulent fluxes are an important source of energy. We inferred higher surface melt rates for Patagonian glaciers as compared to the glaciers of the Central Andes due to a higher contribution of the turbulent sensible heat flux, less negative net longwave radiation and a positive contribution of the turbulent latent heat flux. The variability in the atmospheric emissivity was high and not able to be explained exclusively by the variability in the inferred cloud cover. The influence of the stability correction and the roughness length on the magnitude of the turbulent fluxes in the different climate settings was examined. We conclude that, when working towards physical melt models, it is not sufficient to use the observed melt as a measure of model performance; the model parametrizations of individual components of the energy balance have to be validated individually against measurements.
CRIS-Team WoS Importer:2020-09-11

The 21st-century fate of the Mocho-Choshuenco ice cap in southern Chile - Scheiter, Matthias; Schaefer, Marius; Flandez, Eduardo; Bozkurt, Deniz; Greve, Ralf (Cryosphere, 2021)
Glaciers and ice caps are thinning and retreating along the entire Andes ridge, and drivers of this mass loss vary between the different climate zones. The southern part of the Andes (Wet Andes) has the highest abundance of glaciers in number and size, and a proper understanding of ice dynamics is important to assess their evolution. In this contribution, we apply the ice-sheet model SICOPOLIS (SImulation COde for POLythermal Ice Sheets) to the Mocho-Choshuenco ice cap in the Chilean Lake District (40g g S, 72g g W; Wet Andes) to reproduce its current state and to project its evolution until the end of the 21st century under different global warming scenarios. First, we create a model spin-up using observed surface mass balance data on the south-eastern catchment, extrapolating them to the whole ice cap using an aspect-dependent parameterization. This spin-up is able to reproduce the most important present-day glacier features. Based on the spin-up, we then run the model 80 years into the future, forced by projected surface temperature anomalies from different global climate models under different radiative pathway scenarios to obtain estimates of the ice cap's state by the end of the 21st century. The mean projected ice volume losses are 56±16g % (RCP2.6), 81±6g % (RCP4.5), and 97±2g % (RCP8.5) with respect to the ice volume estimated by radio-echo sounding data from 2013. We estimate the uncertainty of our projections based on the spread of the results when forcing with different global climate models and on the uncertainty associated with the variation of the equilibrium line altitude with temperature change. Considering our results, we project a considerable deglaciation of the Chilean Lake District by the end of the 21st century.
Created from Fastlane, Scopus look-up

The foundations of the Patagonian icefields - Fürst, Johannes; Farías Barahona, David; Blindow, Norbert; Casassa, Gino; Gacitúa, Guisella; Koppes, Michèle; Lodolo, Emanuele; Millan, Romain; Minowa, Masahiro; Mouginot, Jérémie; Pȩtlicki, Michał; Rignot, Eric; et al. (Communications Earth & Environment, 2024)
The two vast Patagonian icefields are a global hotspot for ice-loss. However, not much is known about the total ice volume they store - let alone its spatial distribution. One reason is that the abundant record of direct thickness measurements has never been systematically exploited. Here, this record is combined with remotely-sensed information on past ice thickness mapped from glacier retreat. Both datasets are incorporated in a state-of-the-art, mass-conservation approach to produce a well-informed map of the basal topography beneath the icefields. Its major asset is the reliability increase of thicknesses values along the many marine- and lake-terminating glaciers. For these, frontal ice-discharge is notably lower than previously reported. This finding implies that direct climatic control was more influential for past ice loss. We redact a total volume for both icefields in 2000 of 5351 km3. Despite the wealth of observations used in this assessment, relative volume uncertainties remain elevated.
CRIS-Team Scopus Importer:2024-03-29

Underwater Ice Terrace Observed at the Front of Glaciar Grey, a Freshwater Calving Glacier in Patagonia - Sugiyama, Shin; Minowa, Masahiro; Schaefer, Marius (Geophysical Research Letters, 2019)
Underwater ice geometry at the front of calving glaciers provides crucial information for calving and underwater melting. In this study, we present ice geometry captured by operating a side-scanning sonar near the front of Glaciar Grey, a freshwater calving glacier in Patagonia. The observations revealed ice projecting into the lake with a substantially different structure from that of known tidewater glaciers. Terrace-like ice structures were found at several tens of meters below the water surface and extended up to 100 m from the aerial ice front. The structure depicted by the sonar was confirmed when the ice front was exposed by flotation during a major calving event. We infer that buoyant force acting on the submerged ice terrace acted as a driver of the calving event. Our study demonstrates the importance of the underwater ice geometry, which affects sizable calving at the front of freshwater calving glaciers.
Created from Fastlane, Scopus look-up
Keywords: calving; freshwater calving glacier; glacier; lake; Patagonia; side-scanning sonar